FTIR Spectroscopic Analysis on Air Dried Serum Films of Diseased Kidney and Healthy Subjects - Muthu, S.; Bhaskaran, A.; Sheela, N.R.; Sambathkrishnan, S. (Asian Journal of Chemistry, 2010)
In this paper, the FTIR spectra of serum samples from kidney failure and normal subjects have been recorded over the region 4000-400 cm-1. This method involves drying the serum specimen to a film and comparing the absorption level to characterize the diseased kidney from healthy subject. To substantiate the findings univariate statistical analysis is also made. To quantify the spectral differences intensity ratio parameters are introduced. It is shown that the diseased kidney serum is classified with greater sensitivity and normal with higher specificity.